Preparing Indonesian pre-service English teachers’ readiness to teach through teacher-themed movies (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2022)
This study aimed at examining the extent of the use of teacher-themed movies in preparing Indonesian pre-service English teachers’ readiness to teach and to see the perceived effects of movies in preparing the pre-service English teachers’ readiness to teach. This study employed a qualitative design with observations and interviews as the methods of collecting data. Two classes were observed, Introduction to Education and Teaching Profession classes. Interviews were conducted with, as the participants, six pre-service English teachers and two lecturers of the observed classes. The observation results indicated that movies were used to relate theories and real teaching practices. Through Thematic Analysis of the interview data, the study found that movies could inspire several pre-service English teachers. Movies minimised the gap between theories and practice. Movies helped pre-service teachers to see potential problems and obstacles when teaching in a real class. Informed of the generally positive impacts of the use of movies, it is suggested that teacher education programmes encourage more widespread use of movies to teach teaching-related classes to better prepare pre-service teachers for various classroom situations.